Auditory pitch discrimination in a simple melodic structure in children with autism spectrum disorder - Rojek Zakić, Dajana (Specijalna edukacija i rehabilitacija, 2025)
Introduction. It is suggested that individuals with autism spectrum disorder (ASD) exhibit specific auditory characteristics, such as superior pitch discrimination and increased responsiveness to musical melodies. Objectives. The aim of this research was to determine differences in auditory discrimination of high - and low-pitch melodies in children with ASD. Methods. Auditory pitch discrimination in a simple melodic structure was examined in a sample of thirty children with ASD, aged 7 to 18 years. This ability was tested using an instrument developed for the purposes of this study, which serves as a basis for examining auditory pitch discrimination in melodies in children with ASD. Results. The results of the research indicate that there are differences in the ability to discriminate pitch in a simple melodic structure, with better discrimination of melodies in higher pitch ranges compared to low-pitched melodies (Z = –2.44, p = .015). Autism severity was associated with auditory discrimination of the high-pitch melody, with response quality declining as severity increased (U = 40.50, Z = -2.36, p = .018). Results suggest that children with ASD who demonstrate musical talent exhibit better auditory discrimination (high-pitch: p = .037; low-pitch: p = .035). Age was not associated with the quality of melody pitch discrimination in this sample. Conclusion. The findings highlight the importance of strengthening theoretical knowledge and designing practical approaches that foster the special abilities and overall development of children with ASD.